How I manage severe von Willebrand disease. (9th September 2019) - Leebeek, Frank W. G.; Atiq, Ferdows
Summary: Von Willebrand disease (VWD) is the most common inherited bleeding disorder. Most patients with mild and moderate VWD can be treated effectively with desmopressin. The management of severe VWD patients, mostly affected by type 2 and type 3 disease, can be challenging. In this article we review the current diagnosis and treatment of severe VWD patients. We will also discuss the management of severe VWD patients in specific situations, such as pregnancy, delivery, patients developing alloantibodies against von Willebrand factor and VWD patients with recurrent gastrointestinal bleeding. Moreover, we review emerging treatments that may be applied in future management of patients with severe VWD.